Study on emergency care nurses’ knowledge and attitude towards palliative care (急诊科护士安宁疗护知识和态度的调查研究) - FENG Mei (冯梅) (中西医结合护理)
Objective To investigate the knowledge and attitude towards palliative care among emergency care nurses, and analyze its influencing factors. Methods A questionnaires were conducted among 415 emergency care nurses from tertiary hospitals in Hubei province by using a general information questionnaire, the Hospice Knowledge Quiz for Nurses and the Frommelt Attitudes Toward Care of the Dying Scale Form B (FATCOD-B). Multiple linear step regression was used to analyze the influencing factors. Results The total scores of knowledge and attitude towards palliative care were (12. 44±3. 83) and (97. 35±9. 07), respectively. Sex, professional titles, whether had interactions with a dying patient or not and palliative care training were main factors influencing nurses’ palliative care knowledge. Education level, professional titles and palliative care training were main factors influencing attitude towards palliative care. Conclusion Emergency care nurses had a middle level of knowledge and attitude towards palliative care. More palliative care training including theory and practice should be developed, and nurses with low education level and professional title need to be trained more. (目的 了解急诊科护士安宁疗护知识和态度的现状, 并分析其影响因素。方法 使用一般资料问卷、安宁疗护知识问卷和中文版佛罗梅尔特临终关怀态度量表(FATCOD-B)对便利抽取的湖北省三级医院415名急诊科护士进行调查。使用多元线性逐步回归分析其影响因素。结果 急诊科护士的安宁疗护知识得分为(12. 44±3. 83)分, 安宁疗护态度得分为(97. 35±9. 07)分。性别、职称、是否接触过临终患者及安宁疗护培训是安宁疗护知识的影响因素; 学历、职称及安宁疗护培训是安宁疗护态度的影响因素。结论 急诊科护士安宁疗护知识和态度处于中等水平, 科室应该开展安宁疗护的理论培训和专科实践, 并重点加强对低学历和低职称护士的培训。)